الإرشاد الاجتماعي ومبادئه الأساسية - زريقة، يسرى; عاقل، مجد (جامعة تشرين, 2016)
في ظل ضغوط العالم المتنامية والمشكلات التي أصبحت لا تقوى مواجهتها النفس البشرية بمفردها أصبحت الحاجة ماسة لخدمات الإرشاد الاجتماعي، لذلك فقد انتبهت العديد من المؤسسات الاجتماعية إلى أهمية الاستعانة بالمتخصصين لتلبية هذا المطلب المجتمعي، ولم يعد الإرشاد مجرد خدمة يقدمها شخص لآخر باجتهاد شخصي، بل اتخذ الإرشاد الاجتماعي شكلا منهجيا منظماً، يتطلب شخصا مهنيا ذو مهارات متنوعة شخصية ومهنية وملم بأساليب الإرشاد الاجتماعي ليتمكن من مساعدة المسترشدين وفق أساس علمية مدروسة. تهدف الدراسة الحالية إلى التعرف على مفهوم الإرشاد الاجتماعي ومدى أهميته والأهداف التي يسعى إلى تحقيقها، وسنتعرف على كل من مفهوم المرشد الاجتماعي والمسترشد والخصائص التي يتميز بها المرشد، وبيان المبادئ الأساسية التي تقوم عليها العملية الإرشادية.
Under world pressure growing and the problems that have become not strong enough to confront the human soul alone has become an urgent need for the services of social counseling, so it has realized many of the social institutions to the importance of the use of specialists to meet the community demand, no longer extension just service provided by one person to another personal hard, but social counseling took the form systematically organized, professionally requires people with diverse skills and personal and professional ways mm social counseling to be able to help clients according to scientific bases well thought out. The present study aims to identify the concept of social counseling and the extent of its importance and the objectives it seeks to achieve, and you will learn about all of the concept of social counselor, client and Characteristics which is characterized by social counselor. and the statement of the basic principles upon which the counseling process is indicative.
Keywords: المؤسسات الإجتماعية -- العمليات الإرشادية -- البرامج الإرشادية